Højhave – ein reich ausgestattetes Frauengrab der jüngeren Wikingerzeit bei Hadersleben - Eisenschmidt, Silke (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
In August 2020, a metal detectorist found fragments from a copper-alloy basin and a wooden lid above a ploughed over burial mound, about 7 km south of Haderslev. A trial excavation carried out a few days later could demonstrate that the artifacts came from a 2.0 m wide and minimum 2.6 m long chamber grave aligned southwest-northeast. Only 5 – 10 cm of the fill was preserved. During this trial excavation more fragments of the copper-alloy basin were found, two tongue-shaped Jellinge style brooches, dating to c. 900 – 970 AD, iron fragments of a wooden bucket and other iron fragments. Without doubt, the burial was severely endangered by further ploughing. During the rescue excavation in autumn 2021, it was possible to excavate the grave, financed by The Agency of Culture and Palaces and Museum Sønderjylland. Although the base of the grave was only few centimetres below the topsoil, skeletal remains were preserved, and the artifacts were still in situ. The deceased woman lay in the middle of the 5.4 m² large wooden chamber. In addition to the objects already mentioned, the grave also contained a wooden casket, a key, a game board, a knife, a pair of shears, glass beads, silver fragments, and a third brooch. The chamber grave from Højhave is one of the most well-equipped women’s graves from Viking age Denmark.